Online and Offline Friendship Among Italian Adolescent Girls - Zucchetti, Giulia; Giannotta, Fabrizia; Rabaglietti, Emanuela (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology, 2013)
Background: There is still a question of whether online friendship predicts changes in face-to-face friendship (Reduction Hypothesis) or face-to-face friendship predicts changes in online friendship (Compensation Hypothesis) during adolescence. Objective: The purpose of this study was to compare these two hypotheses to determine which comes first: online friendship or offline friendship. Method: Eighty adolescent girls between the ages of 14 and 19 years (mean, 16.07 years; standard deviation, 1.28 years) on a non-traditional school track completed self-report questionnaires. Two wave longitudinal models were tested with the use of cross-lagged analysis to compare the hypotheses. Results: Analysis showed that negative face-to-face friendship quality predicted online friendship but that the opposite was not true. Conclusions: The study’s findings underlined the compensation role of online friendship for girls with poor or unsatisfactory offline social worlds. The implications of this information and suggestions for clinicians and professionals to use to enhance adolescent social skills and to promote appropriate use of the Internet will be discussed.